The Anxiety and Defense Mechanism on Claireece Precious Jones’ Character in Precious Film (2009) - Supiansyah, Selvia; Valiantien, Nita Maya; Sanhadi Rahayu, Famala Eka (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
The purposes of this study are to find out the types of anxiety in Claireece Precious Jones character in Precious film and to describe how Claireece Precious Jones act against her anxiety by using defense mechanism. The data were analyzed by using the theory of anxiety and defense mechanism by Sigmund Freud. This study used qualitative method and the data the data were generated from dialogues from the film script. The findings of this study showed that Claireece experienced three types of anxiety. First, neurotic anxiety as indicated by halucination. The anxiety arose when she had a flashback about what happened to her situation in the home when she beaten and scolded at home by her mother. Second, moral anxiety which was indicated by the feeling of guilty and fail to do what is considered morally right. Third, she experienced realistic anxiety which was shown when she expelled her teacher because she was afraid of being beaten and scolded by her mother if she went out to meet her teacher. Claireece tried to fight her anxiety with five defense mechanism there are repression, denial, projection, reaction formation, and displacement.